A multi-criterion approach to optimal vaccination planning: Method and solution. (December 2018) - Ng, C.T.; Cheng, T.C.E.; Tsadikovich, Dmitry; Levner, Eugene; Elalouf, Amir; Hovav, Sharon
Highlights: We formulated the multi-criteria problem of optimal vaccine distribution. We solved the problem using the modified epsilon-constraint method. We solved large-sized instances using real-life data from the HCO CLALIT (Israel). Targeted vaccination strategy is more effective than the mass and random strategies. The Pareto-optimal solutions outperform the corresponding single-criterion solutions. Abstract: Seasonal influenza is a serious public health concern, against which vaccination is one of the most effective ways to protect people. However, the effect of vaccination on containing influenza spread critically depends on the immunization programme adopted. Therefore, the problem of finding the optimal combination of vaccination strategies, with a view to decreasing the programme cost, enhancing vaccination efficiency, and improving societal benefits, is of great theoretical and practical importance. We develop a multiple criteria mathematical programming model to address the problem, analyze the model, and derive the structural properties of the optimal solution. Conducting extensive numerical studies to assess the merit of the model, we find that an integrated strategy embracing early-stage indiscriminate mass vaccination with late-stage targeted vaccination outperforms other strategies in cost and efficacy.